2021
DOI: 10.3390/ani11102828
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Antimicrobial Use on Irish Pig Farms

Abstract: The threat to public health posed by antimicrobial resistance in livestock production means that the pig sector is a particular focus for efforts to reduce antimicrobial use (AMU). This study sought to investigate the risk factors for AMU in Irish pig production. Antimicrobial use data were collected from 52 farrow-to-finish farms. The risk factors investigated were farm characteristics and performance, biosecurity practices, prevalence of pluck lesions at slaughter and serological status for four common respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(105 reference statements)
0
0
0
Order By: Relevance
“…Herd-level antimicrobial prescription data from Danish organic pig herds were analyzed for associations with abattoir meat inspection findings, but no significant results emerged [ 27 ]. In another study, no direct association was observed between the total AMU on Irish farrow-to-finish pig farms and the prevalence of pneumonia and pleurisy at slaughter, but positive associations were found with the prevalence of pericarditis, lung abscesses and liver milk spots [ 8 ]. In the present study, although the EP score did not vary with the total AMU, it was positively associated with the usage of macrolides and critical classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herd-level antimicrobial prescription data from Danish organic pig herds were analyzed for associations with abattoir meat inspection findings, but no significant results emerged [ 27 ]. In another study, no direct association was observed between the total AMU on Irish farrow-to-finish pig farms and the prevalence of pneumonia and pleurisy at slaughter, but positive associations were found with the prevalence of pericarditis, lung abscesses and liver milk spots [ 8 ]. In the present study, although the EP score did not vary with the total AMU, it was positively associated with the usage of macrolides and critical classes.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of respiratory tract lesions is also of great interest, as the porcine respiratory disease complex (PRDC) represents a major economical, health and welfare problem in pig production worldwide [ 7 ]. Furthermore, PRDC is one of the main drivers of antimicrobial use (AMU) in pig farming [ 8 ]. The most prevalent lung lesions in slaughtered pigs are cranioventral pulmonary consolidation (CVPC) and chronic pleuritis, as reported in several studies [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation